Double simultaneous intussusception caused by Meckel's diverticulum and intestinal duplication in a child. Issue 8 (August 2018) - Yu, Mingming; Fang, Zhihong; Shen, Jun; Zhu, Xiaomin; Wang, Dafeng; Shi, Yingzuo
Intussusception is common in children. Double simultaneous intussusception is a peculiar variety of intussusception with only 14 previously reported cases. We report a unique case of a child who suffered from double simultaneous intussusception with two lead points (Meckel's diverticulum and intestinal duplication). The patient was successfully treated with manual reduction along with resection of Meckel's diverticulum and intestinal duplication. The child recovered well.